The Effect Of Business Risk, and Financial Risk on Profitability in Mining Sector Companies Listed on The Indonesia Stock Exchange (IDX) for The 2018-2021 Period - Jesyca Ireyne Duru; Usil Sis Sucahyo (Return : Study of Management, Economic and Bussines, 2023)
The purpose of this study is to determine how much influence Total Asset Turnover, Debt to Equity Ratio, has on Return On Equity in mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The researcaes take a total of 60 Sample is done by purposive sampling technique. This research uses quantitative methods with descriptive analysis techniques using SPSS version 20 software.the data used is secondary data and obtained through the official website of the Indonesia Stock Exchange (IDX) in the form of annual financial statements (www.idx.co.id). Through this research, it was found that Total Asset Turnover had a significant positive effect on Return On Equity in mining sub-sector companies. Meanwhile, the Debt to Equity Ratio has a significant negative effect on Return On Equity in mining sub-sector companies.